Women's Financial Literacy: Perceived Financial Knowledge and Its Impact on Money Management - Gunawan, Vincent; Dewi, Vera Intanie; Iskandarsyah, Triyana; Hasyim, Irsanti (UI Scholars Hub, 2021)
This paper presents an empirical study on women's financial literacy in a developing country, Indonesia. Financial literacy in developing countries, especially for women, needs to be improved. Traditionally, women have an important role in managing family's finances. Their ability to conduct good financial management can help their family's financial stability and improve its welfare. If women do not have adequate capacity to manage the family finances, the family's economic health can be at risk. Having financial literacy is important as it provides financial resilience at times of uncertainty. This explanatory research uses a sample comprising 100 women living in the city of Bandung, Indonesia, who are in the Baby Boomer generation as well as in Generations X, Y, and Z. The data were collected through an online questionnaire and analyzed using partial least squares structural equation modeling (PLS-SEM). The results provide evidence that perceived financial knowledge has a significant effect on financial management behavior in the dimensions of savings behavior, shopping behavior, long-term planning, and short-term planning. Moreover, the study results show that the respondents have a moderate level of financial literacy and financial management behavior.